2016
DOI: 10.1080/09712119.2016.1264305
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of the effect of Cowpea (Vigna unguiculata) phenolic extract in bovine peripheral blood

Abstract: View related articles View Crossmark data Citing articles: 4 View citing articles Microarray analysis of the effect of Cowpea (Vigna unguiculata) phenolic extract in bovine peripheral blood

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Pulses are a vital source of plant-based proteins and amino acids for people around the globe and may be eaten as part of a healthy diet to address obesity, as well as to prevent and help manage chronic diseases such as diabetes, coronary conditions and cancer; they are also an important source of plant-based protein for animals [6,117]. In a study of the phenolic content and antioxidant properties of selected cowpea varieties tested in bovine peripheral blood.…”
Section: Effects Of Water Stress On Grain Nutrient Content and Phytocmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulses are a vital source of plant-based proteins and amino acids for people around the globe and may be eaten as part of a healthy diet to address obesity, as well as to prevent and help manage chronic diseases such as diabetes, coronary conditions and cancer; they are also an important source of plant-based protein for animals [6,117]. In a study of the phenolic content and antioxidant properties of selected cowpea varieties tested in bovine peripheral blood.…”
Section: Effects Of Water Stress On Grain Nutrient Content and Phytocmentioning
confidence: 99%
“…Adjei-Fremah et.al. [118] reported that, the potential of cowpea polyphenols to reduce oxidative stress in livestock production is high which is a positive indication for human health improvement. Viets [119] and Alam [120] reported that, drought reduces both nutrient uptake by the roots and transport from the roots to the shoots, because of restricted transpiration rates and impaired active transport and membrane permeability, the decline in soil moisture also results in a decrease in the diffusion rate of nutrients in the soil to the absorbing root surface [121,122].…”
Section: Effects Of Water Stress On Grain Nutrient Content and Phytocmentioning
confidence: 99%
“…Epigallocatechin-3-gallate, a flavonoid found in green tea, has been shown to inhibit NF-κB activation induced by many proinflammatory stimuli [67]. Recently, there is a great interest in feed polyphenols due to their antioxidant capacity, inflammatory and immunomodulatory properties and their possible beneficial implications on animal health and production [7,54,68,69,79].…”
Section: Plant Polyphenolsmentioning
confidence: 99%
“…Reverse transcription was performed using Oligo (dT) primers with 2 ug of the total RNA from each treatment group using a Complementary DNA (cDNA) RETRO script Kit (Ambion Inc., Austin, TX) following the manufacturer's instructions as previously described by Adjei-Fremah et al, 2016c. The cDNA products were measured for purity and concentration using the Nanodrop spectrophotometer (NanoDrop Technologies).…”
Section: Real-time Pcrmentioning
confidence: 99%